Functional characterization of enhancer activity during a long terminal repeat's evolution - Du, Alan Y.; Zhuo, Xiaoyu; Sundaram, Vasavi; Jensen, Nicholas O.; Chaudhari, Hemangi G.; Saccone, Nancy L.; Cohen, Barak A.; Wang, Ting (Genome Research, 2022)
Many transposable elements (TEs) contain transcription factor binding sites and are implicated as potential regulatory elements. However, TEs are rarely functionally tested for regulatory activity, which in turn limits our understanding of how TE regulatory activity has evolved. We systematically tested the human LTR18A subfamily for regulatory activity using massively parallel reporter assay (MPRA) and found AP-1- and CEBP-related binding motifs as drivers of enhancer activity. Functional analysis of evolutionarily reconstructed ancestral sequences revealed that LTR18A elements have generally lost regulatory activity over time through sequence changes, with the largest effects occurring owing to mutations in the AP-1 and CEBP motifs. We observed that the two motifs are conserved at higher rates than expected based on neutral evolution. Finally, we identified LTR18A elements as potential enhancers in the human genome, primarily in epithelial cells. Together, our results provide a model for the origin, evolution, and co-option of TE-derived regulatory elements.